What Happened After the 2012 Shift in Canadian Copyright Law? An Updated Survey on How Copyright is Managed across Canadian Universities - Graham, Rumi; Winter, Christina (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2017)
Objective – The purpose of this study is to understand the practices and approaches followed by Canadian universities in copyright education, permissions clearance, and policy development in light of major changes to Canadian copyright law that occurred in mid-2012. The study also seeks to identify aspects of copyright management perceived by the universities to be challenging.Methods – In 2015, an invitation to complete an online survey on institutional copyright practices was sent to the senior administrator at member libraries of Canada’s four regional academic library consortia. The invitation requested completion of the survey by the person best suited to respond on behalf of the institution. Study methods were largely adapted from those used in a 2008 survey conducted by another researcher who targeted members of same library consortia.Results – While the university library maintained its leadership role in copyright matters across the institution, the majority of responding institutions had delegated responsibility for copyright to a position or office explicitly labeled copyright. In contrast, respondents to the 2008 survey most often held the position of senior library administrator. Blanket licensing was an accepted approach to managing copyright across Canadian universities in 2008, but by 2015 it had become a live issue, with roughly half of the respondents indicating their institutions had terminated or were planning to terminate their blanket license.Conclusion – In just seven years we have witnessed a significant increase in specialized attention paid to copyright on Canadian university campuses and in the breadth of resources dedicated to helping the university community understand, comply with, and exercise various provisions under Canadian copyright law, which include rights for creators and users.